Three Hundred Years of Perm – Three Hundred Years of Development of Perm Pharmacy - article Editorial (Разработка и регистрация лекарственных средств, 2023)
In 2023, the 300th anniversary of the founding of the city of Perm was celebrated. During this period, various areas of medicine and pharmacy in the region were formed. Pharmacists took an active part in the formation of many areas. During the years of formation of the new healthcare model “Semashko System”, teachers of the first center of pharmaceutical education in the Urals made a great contribution. The analysis of historical sources carried out by the authors made it possible to assess the path traveled by the pharmacy of the Kama region. Purpose: To identify and analyze of trends in the development of Perm pharmacy over the past 300 years since the founding of Perm. Materials and methods. The following objects of study were used: abstracts stored in the archives of the Perm State Pharmaceutical Academy (PSPhA); university reports stored in the archives of the museum of PSPhA; book and journal publications, materials of congresses of doctors and representatives of zemstvos of the Perm province. The research methods were: documentary analysis, methods of one-factor analysis: summary, grouping. Results. During the study, materials on the creation and development of various areas of medicine and pharmacy in the Perm region were studied. The directions of work of scientists at the Center for Pharmaceutical Education in the Urals on the formation of institutions of higher and secondary pharmaceutical education, methods and forms of advanced training for practical specialists are highlighted.